2008
DOI: 10.7326/0003-4819-149-5-200809020-00005
|View full text |Cite
|
Sign up to set email alerts
|

Total and High-Molecular-Weight Adiponectin and Resistin in Relation to the Risk for Type 2 Diabetes in Women

Abstract: Background Adiponectin, particularly high-molecular weight adiponectin, and resistin are recently discovered adipokines that may provide a molecular link between adiposity and type 2 diabetes. Objective To evaluate whether total and high-molecular weight adiponectin and resistin are associated with the future risk for type 2 diabetes, independent of obesity and other known diabetes risk factors. Design Prospective, nested case-control study. Settings United States. Participants 1,038 initially healthy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
149
4
5

Year Published

2009
2009
2014
2014

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 192 publications
(168 citation statements)
references
References 47 publications
10
149
4
5
Order By: Relevance
“…For example, mutations that inhibit the formation of high-molecular-weight adiponectin lead to type 2 diabetes, suggesting that this isoform may be a better predictor of insulin resistance and diabetes than total adiponectin, as reported recently. (32) Since the assay used in this study measured total adiponectin levels, we were unable to determine the relative contribution of different isoforms to the associations with the parameters related to skeletal development that we observed. A further limitation to this study was the use of self-assessment by questionnaire to evaluate pubertal stage as opposed to evaluation by a trained examiner.…”
Section: à006)mentioning
confidence: 72%
“…For example, mutations that inhibit the formation of high-molecular-weight adiponectin lead to type 2 diabetes, suggesting that this isoform may be a better predictor of insulin resistance and diabetes than total adiponectin, as reported recently. (32) Since the assay used in this study measured total adiponectin levels, we were unable to determine the relative contribution of different isoforms to the associations with the parameters related to skeletal development that we observed. A further limitation to this study was the use of self-assessment by questionnaire to evaluate pubertal stage as opposed to evaluation by a trained examiner.…”
Section: à006)mentioning
confidence: 72%
“…Adiponectin, a hormone exclusively secreted by adipocytes, circulates abundantly in the bloodstream, as low, medium and high molecular weight (LMW, MMW and HMW) multimers [4,5] and has well-recognised antiatherogenic, anti-inflammatory and insulin-sensitising properties [4,6]. Studies in humans have persistently reported that insulin resistance and related clinical outcomes are associated with lower adiponectin concentrations [7][8][9] as well as with increased UAE [10,11]. Based upon these well established associations, one would expect an inverse relationship between circulating adiponectin and albuminuria.…”
Section: Introductionmentioning
confidence: 99%
“…In the majority of studies, total and HMW adiponectin are reduced in obesity and type 2 diabetes and show stronger association with insulin resistance, risk of type 2 diabetes and coronary artery diseases than MMW and LMW adiponectin (32,33,34,35,36,37,38). In this context, the finding of normal total and HMW adiponectin and the relative increase in the fraction of HMW adiponectin and the decrease in absolute levels and fraction of LMW adiponectin may play a beneficial role for the Arg1174Gln carriers.…”
Section: Discussionmentioning
confidence: 99%